A STUDY IN YELLOW: THE CASE OF THE HIDDEN HYPHAE. (29th November 2012) - Turnbull, H; Pereira, A
Abstract : A 24-year-old female Punjabi student came to the UK in 2010. A right hilar mass on routine CXR and respiratory physicians performed mediastinoscopy. Right paratracheal lymph node histology demonstrated non-caseating granulomatous lymphadenitis with central necrosis. TB culture was negative. She was well and followed up with presumed quiescent sarcoidosis or TB. In September 2011, she reported 2 months of headache, 5 weeks of right eye swelling and a persistent cough. She had a right exopthalmos with left-sided weakness especially the arm. MRI brain demonstrated six enhancing intra-axial masses within the right hemisphere, six in the cerebellum and one lesion extending into the medulla. Abnormal tissue expanded into the right orbit causing exopthalmos. HIV status was negative and she was not diabetic. She was commenced on steroids and empirical quadruple therapy for TB. The presumed differentials were sarcoidosis, TB or possible malignancy Bone marrow trephine was normal (no evidence of lymphoma or organisms). Biopsy of the orbital lesion contained numerous, well preserved, fungal hyphae within the granulomas. IgE was 2000 kU/L (0–81), aspergillus precipitins >200 (0–40). Culture was positive for aspergillus flavus. Histological re-examination of the original chest lesion also confirmed aspergillus hyphae. This is a case of disseminated aspergillus infection. The patient responded well to antifungal treatment with ambisome, andulifungin IV, voroconizole and dexamethsone with resolution clinically and radiologically.